Pertanggungjawaban Terhadap Perlindungan Konsumen atas Peredaran Emas Ilegal - Kartiko, Nafis Dwi; Soegiono, Samuel Putra; Indradewi, Astrid Athina (Indonesian Journal Publisher, 2024)
Consumer protection law plays a crucial role in safeguarding the rights and interests of consumers in various sectors by ensuring fair trade practices, product safety, preventing fraud, and building trust between consumers and businesses. This research aims to analyse legal liability in the context of consumer protection against illegal gold circulation. This research uses a normative-dogmatic juridical research method. The results show that there is a significant violation of consumers' right to correct and accurate information, which affects their purchasing and investment decisions. The research suggests the need for greater transparency and the application of stricter sanctions to prevent similar incidents in the future. The theoretical implications of this research strengthen the understanding of the application of consumer protection law in real practice, while its practical implications emphasise the importance of industry compliance with legal standards to maintain consumer confidence and market integrity.